ANALYSIS OF THE IMPLEMENTATION OF MONEY LOAN TRANSACTION BUSINESS IN MITRA BISNIS KELUARGA VENTURE ACCORDING TO ISLAMIC ECONOMICS - Aulia, Lia; Nawawi, Kholil; Suhandi, Tjeptjep (Program Studi Ekonomi Islam FEI UNIDA Bogor, 2018)
This study aims to find out how the review of Islamic Economics is seen from the contract in accordance with sharia principles on the implementation of loan transactions for Venture Family Business Partners in Situ Udik Village, Cibungbulang District, Bogor. This type of research is descriptive qualitative research with exposure related to existing problem solving. The results of this study indicate, according to the review of Islamic Economics, seen from the analysis of the contract, the MBK Ventura money loan does not use a contract that is in accordance with sharia principles but uses the Grameen Bank system. Grameen Bank is the provision of unsecured loans that are devoted to the poor. This 20% profit sharing shows an additional loan from MBK Ventura's capital money for MBK Ventura itself. 20% is said to contain elements of usury, because in practice there is no contract in accordance with sharia principles. From the community response, it was shown that, successful or unsuccessful in using money for business capital, still had to pay a return on capital with an additional 20%. Thus, the implementation of the MBK Ventura money loan transaction is not permitted in Islam, because there is an addition to each loan including usury